Canonical sonic Hedgehog signaling in early lung development - Silva, Hugo Miguel Fernandes (2017)
The canonical hedgehog (HH) signaling pathway is of major importance during embryonic development. HH is a key regulatory morphogen of numerous cellular processes, namely, cell growth and survival, differentiation, migration, and tissue polarity. Overall, it is able to trigger tissue-specific responses that, ultimately, contribute to the formation of a fully functional organism. Of all three HH proteins, Sonic Hedgehog (SHH) plays an essential role during lung development. In fact, abnormal levels of this secreted protein lead to severe foregut defects and lung hypoplasia. Canonical SHH signal transduction relies on the presence of transmembrane receptors, such as Patched1 and Smoothened, accessory proteins, as Hedgehog-interacting protein 1, and intracellular effector proteins, like GLI transcription factors. Altogether, this complex signaling machinery contributes to conveying SHH response. Pulmonary morphogenesis is deeply dependent on SHH and on its molecular interactions with other signaling pathways. In this review, the role of SHH in early stages of lung development, specifically in lung specification, primary bud formation, and branching morphogenesis is thoroughly reviewed.